1982
DOI: 10.1530/jrf.0.0650141
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of a major, low molecular weight protein released by the trophoblast of sheep blastocysts at Day 13-21

Abstract: Sheep blastocysts (Day 13-21) incubated in a modified Minimum Essential Medium released proteins into the medium at an approximately linear rate over a 24-h period. Single Day-16 blastocysts converted 2-8% of the radioactivity supplied (100 muCi L-[3H]leucine) into non-dialysable macromolecules which were released into the medium. Two-dimensional polyacrylamide gel electrophoresis revealed that at Day 13 there was only one major product (Protein X), consisting of three closely similar isoelectric species of (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
177
0
1

Year Published

1983
1983
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 332 publications
(184 citation statements)
references
References 12 publications
6
177
0
1
Order By: Relevance
“…Because of the abundance of trophoblastic cells, as compared to the very small number of endodermic cells, and because of their very high secretory activity, the secretion of signals inhibiting luteolysis seems likely to take place in the trophectoderm, the endodermic tissue playing the essential role of sus¬ taining the trophectoderm, although endodermic cells are probably also necessary for continued growth of trophectoderm as shown in the mouse (Ilgren, 1981). Amongst these signals, trophoblastin is an antiluteolytic protein whose biochemical nature is still unknown (Martal et al, 1979) although it might correspond to the protein X of Godkin, Bazer, Moffatt, Sessions & Roberts (1982).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the abundance of trophoblastic cells, as compared to the very small number of endodermic cells, and because of their very high secretory activity, the secretion of signals inhibiting luteolysis seems likely to take place in the trophectoderm, the endodermic tissue playing the essential role of sus¬ taining the trophectoderm, although endodermic cells are probably also necessary for continued growth of trophectoderm as shown in the mouse (Ilgren, 1981). Amongst these signals, trophoblastin is an antiluteolytic protein whose biochemical nature is still unknown (Martal et al, 1979) although it might correspond to the protein X of Godkin, Bazer, Moffatt, Sessions & Roberts (1982).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, conceptuses were cultured under serum-free conditions in presence of a radioactive amino acid for about 24 hours, and proteins released into the medium analyzed by two-dimensional PAGE. These experiments immediately revealed that the major secretory product released by the unattached sheep conceptus was a protein of molecular weight approximately 18,000, which consisted of several forms differing slightly in isoelectric point (7). The production of this protein, which was maximal at about day 15, became undetectable after the end of the third week of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…3). Only in the latter preparation did we detect ovine trophoblast protein-1 which we have previously shown to be the major product secreted into culture medium by whole sheep blastocysts (Godkin et al, 1982a;Godkin, Bazar & Roberts, 1984). The polypeptides (numbered 1-4) produced in major amounts by all the preparations were identical in mobility to polypeptides found in fetal sheep plasma (PI.…”
Section: Cell Culturesmentioning
confidence: 72%
“…The proteins synthesized in vitro by sheep and pig blastocysts during the pre-, peri-and post-attachment periods have been described and some of the proteins that were released into the culture medium have been purified and characterized (Godkin, Bazer, Moffatt, Sessions & Roberts, 1982a;Godkin, Bazer, Geisert, Lewis & Roberts, 1982b;Masters et al, 1983). However, the yield of such proteins is relatively small and their preparation is time consuming and expensive.…”
Section: Introductionmentioning
confidence: 99%